2020
DOI: 10.18203/2394-6040.ijcmph20200425
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of vaccine cold chain handlers about vaccine cold chain in district Etawah

Abstract: Background: Vaccine potency can be lost when exposed to non-recommended temperatures. Hence for the proper running of the universal immunization programme (UIP) factors like vaccine cold chain and vaccine management wants great focus and attention skills and knowledge of the vaccine cold chain handlers so for good implementation of UIP vaccine cold chain handlers are important.Methods: This was an observational cross-sectional study. Study duration was carried out from October 2017 to March 2018. All the 16 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This finding is nearly similar to a study done in the Jimma zone in which 62.3% of health professionals knew the compartment of the measles vaccine [ 1 ]. This is lower than the studies done in Central Ethiopia [ 49 ], the Ezha district of the Gurage zone [ 46 ], and Mozambique [ 19 ]. This discrepancy might be due to an absence or insufficient training, workload, or staff turnover.…”
Section: Discussionmentioning
confidence: 59%
“…This finding is nearly similar to a study done in the Jimma zone in which 62.3% of health professionals knew the compartment of the measles vaccine [ 1 ]. This is lower than the studies done in Central Ethiopia [ 49 ], the Ezha district of the Gurage zone [ 46 ], and Mozambique [ 19 ]. This discrepancy might be due to an absence or insufficient training, workload, or staff turnover.…”
Section: Discussionmentioning
confidence: 59%
“…12,13 Proper cold chain management is considered as one indicator of an effective immunization program. [14][15][16] Vaccines are delicate biological molecules that irreversibly lose potency and efficiency when exposed to temperatures outside the recommended ranges. 17,18 The quality of the vaccine is maintained using a cold chain that meets specific temperature requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Adebimpe and Adeoye 9 in Nigeria, found that the majority over half had practiced for 1-6 years and were practicing in urban region. Mohammed et al, 10 found that there were 66.9% male respondents, 37.8% were diplomas, while 62.2% had a degree of work experience ranging from 4 months to 14 years Kumar et al, 11 in an observational cross-sectional study in Etawah found that all respondents were male and approximately one-third were post-graduate Kumar et al, 7 showed that among cold chain handlers of all the 29 PHCs, where In the present study, it was observed that the correct knowledge regarding internet-based eVIN, vaccine's placement in the freezer compartment of domestic refrigerator, keeping items other than vaccines in ILR or DF, the conditioning of icepacks, keeping vaccines away from walls in vaccine carriers, and correct place of thermometer in ILR/DF was correctly given by all of the CCHs, while knowledge about AEFI, its primary management, about a hold over time, and keeping dropper in ILR were given least correctly. Similar studies show that the overall level of good knowledge of vaccine handlers and good status of cold chain and vaccine management was in approximately half of the participants Gebretnsae et al, 12 Mohammed et al, 10 found that approximately half of vaccinators and vaccine handlers had satisfactory knowledge, positive attitude, and good practice, Kumar et al,11 in an observational and cross-sectional study in Etawah and found that all of the cold chain handlers interviewed had the knowledge of vaccine cold chain and most of them had knowledge of temperature range for vaccine storage.…”
Section: Discussionmentioning
confidence: 99%
“…Mohammed et al, 10 found that there were 66.9% male respondents, 37.8% were diplomas, while 62.2% had a degree of work experience ranging from 4 months to 14 years Kumar et al, 11 in an observational cross-sectional study in Etawah found that all respondents were male and approximately one-third were post-graduate Kumar et al, 7 showed that among cold chain handlers of all the 29 PHCs, where In the present study, it was observed that the correct knowledge regarding internet-based eVIN, vaccine's placement in the freezer compartment of domestic refrigerator, keeping items other than vaccines in ILR or DF, the conditioning of icepacks, keeping vaccines away from walls in vaccine carriers, and correct place of thermometer in ILR/DF was correctly given by all of the CCHs, while knowledge about AEFI, its primary management, about a hold over time, and keeping dropper in ILR were given least correctly. Similar studies show that the overall level of good knowledge of vaccine handlers and good status of cold chain and vaccine management was in approximately half of the participants Gebretnsae et al, 12 Mohammed et al, 10 found that approximately half of vaccinators and vaccine handlers had satisfactory knowledge, positive attitude, and good practice, Kumar et al,11 in an observational and cross-sectional study in Etawah and found that all of the cold chain handlers interviewed had the knowledge of vaccine cold chain and most of them had knowledge of temperature range for vaccine storage. Among the 34 cold chain handlers the skills in the identification of light-sensitive vaccines, stages of VVM, checking of ice thickness, precautions of using a dropper, arranging vaccines to temperature sensitivity, labeling of open vials both multidose and open vial policy, condition of ice packs, proper disposal of vials, and preventing of vaccines from touching the walls were able to perform splendidly by all of the cold chain handlers while in tasks of using eVIN application, placing thermometer, reading of temperature, performing shake test, entry of temperature data into the logs, and preparing AEFI kit was only be able to perform by approximately a quarter of them.…”
Section: Discussionmentioning
confidence: 99%